Contextualizing the Kacapi Instrument in Karungut Tradition: A Reflection of Indonesian Art Education Paradigm through Ki Hadjar Dewantara’s Philosophy - Elvionita Surya, Dhea; Uus Karwati; Reni Haerani (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the pedagogical and philosophical meanings contained in the kacapi instrument in the Karungut oral tradition of the Dayak Ngaju people in Central Kalimantan and its relevance to Ki Hadjar Dewantara's philosophy of education. Using descriptive-ethnographic qualitative methods, this study explores the symbolic and moral dimensions of the kacapi instrument and Karungut as a form of cultural pedagogy. The results show that the kacapi functions not only as a musical accompaniment, but also as a symbol of balance, spirituality, and wisdom, which is embodied through symbolic ornaments such as Batang Garing and Burung Enggang. This representation is in line with Ki Hadjar Dewantara's three principles of education, namely Ing Ngarso SungTulodo, Ing Madyo Mangun Karso, and Tut Wuri Handayani, which emphasize character building through exemplary behavior, guidance, and freedom of expression. Thus, the recontextualization of the kacapi in the Karungut tradition becomes a form of culture-based arts education that fosters moral character, ecological awareness, and cultural identity.